Bio-Based Polyurethane Foams: Feedstocks, Synthesis, and Applications - Marta Santos; Marcos Mariz; Igor Tiago; Susana Alarico; Paula Ferreira (Biomolecules)
Polyurethanes (PUs) are extremely versatile materials used across different industries. Traditionally, they are synthesized by reacting polyols and isocyanates, both of which are petroleum-derived reagents. In response to the demand for more eco-friendly materials, research has increasingly focused on developing new routes for PU synthesis using renewable feedstocks. While substituting isocyanates remains a greater challenge, replacing fossil-based polyols with bio-based alternatives is now a promising strategy. This review explores the main natural sources and their transformations into bio-polyols, the incorporation of bio-fillers into PU formulations, and the production of non-isocyanate polyurethanes (NIPUs). Additionally, the study summarizes the growing body of research that has reported successful outcomes using bio-polyols in PU foams for distinct applications.